Developing drugs that target the Wnt pathway: recent approaches in cancer and neurodegenerative diseases. (1st February 2017) - Serafino, Annalucia; Sferrazza, Gianluca; Colini Baldeschi, Arianna; Nicotera, Giuseppe; Andreola, Federica; Pittaluga, Eugenia; Pierimarchi, Pasquale
ABSTRACT: Introduction: Wnt/β-catenin signaling is an evolutionarily conserved pathway that has a crucial role in embryonic and adult life. Dysregulation of Wnt/β-catenin pathway has been associated with various diseases, including cancer and neurodegenerative disorders, including Parkinson's disease (PD). Several molecular components of the signaling have been proposed as innovative targets for cancer therapy, and very recently, some of them have been also evaluated as potential therapeutic targets for PD. Areas covered: This review focuses on the role of Wnt/β-catenin pathway in the pathogenensis of cancer and PD, examining some recent therapeutic approaches that are ongoing in preclinical and clinical studies. The possibilities that this signaling offers for diagnosis and prognosis of neoplastic diseases, and the concerns of targeting this pathway are also discussed. Expert opinion: Despite the stimulating results obtained in preclinical studies on cancer and other disease models, the clinical experience with Wnt modulators is still in its infancy, and is mainly restricted to anticancer therapy. Even with concerns of the safety of drugs targeting Wnt signaling, the attention of researchers worldwide is increasing to this issue in terms of their therapeutic potential for diseases such as PD, for which no cure exists.